Attribution of Extreme Weather Events in the Context of Climate Change - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
As climate has warmed over recent years, a new pattern of more frequent and more intense weather events has unfolded across the globe. Climate models simulate such changes in extreme events, and some of the reasons for the changes are well understood. Warming increases the likelihood of extremely hot days and nights, favors increased atmospheric moisture that may result in more frequent heavy rainfall and snowfall, and leads to evaporation that can exacerbate droughts. Even with evidence of these broad trends, scientists cautioned in the past that individual weather events couldn't be attributed to climate change. Now, with advances in understanding the climate science behind extreme events and the science of extreme event attribution, such blanket statements may not be accurate. The relatively young science of extreme event attribution seeks to tease out the influence of human-cause climate change from other factors, such as natural sources of variability like El Niño, as contributors to individual extreme events. Event attribution can answer questions about how much climate change influenced the probability or intensity of a specific type of weather event. As event attribution capabilities improve, they could help inform choices about assessing and managing risk, and in guiding climate adaptation strategies. This report examines the current state of science of extreme weather attribution, and identifies ways to move the science forward to improve attribution capabilities.
Keywords: Earth Sciences; Environment and Environmental Studies

Frontiers in Decadal Climate Variability: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Many factors contribute to variability in Earth's climate on a range of timescales, from seasons to decades. Natural climate variability arises from two different sources: (1) internal variability from interactions among components of the climate system, for example, between the ocean and the atmosphere, and (2) natural external forcings, such as variations in the amount of radiation from the Sun. External forcings on the climate system also arise from some human activities, such as the emission of greenhouse gases (GHGs) and aerosols. The climate that we experience is a combination of all of these factors. Understanding climate variability on the decadal timescale is important to decision-making. Planners and policy makers want information about decadal variability in order to make decisions in a range of sectors, including for infrastructure, water resources, agriculture, and energy. In September 2015, the National Academies of Sciences, Engineering, and Medicine convened a workshop to examine variability in Earth's climate on decadal timescales, defined as 10 to 30 years. During the workshop, ocean and climate scientists reviewed the state of the science of decadal climate variability and its relationship to rates of human-caused global warming, and they explored opportunities for improvement in modeling and observations and assessing knowledge gaps. Frontiers in Decadal Climate Variability summarizes the presentations and discussions from the workshop.
Keywords: Earth Sciences

Open Science by Design: Realizing a Vision for 21st Century Research - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Openness and sharing of information are fundamental to the progress of science and to the effective functioning of the research enterprise. The advent of scientific journals in the 17th century helped power the Scientific Revolution by allowing researchers to communicate across time and space, using the technologies of that era to generate reliable knowledge more quickly and efficiently. Harnessing today's stunning, ongoing advances in information technologies, the global research enterprise and its stakeholders are moving toward a new open science ecosystem. Open science aims to ensure the free availability and usability of scholarly publications, the data that result from scholarly research, and the methodologies, including code or algorithms, that were used to generate those data. Open Science by Design is aimed at overcoming barriers and moving toward open science as the default approach across the research enterprise. This report explores specific examples of open science and discusses a range of challenges, focusing on stakeholder perspectives. It is meant to provide guidance to the research enterprise and its stakeholders as they build strategies for achieving open science and take the next steps.
Keywords: Policy for Science and Technology

The Future of Atmospheric Chemistry Research: Remembering Yesterday, Understanding Today, Anticipating Tomorrow - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Our world is changing at an accelerating rate. The global human population has grown from 6.1 billion to 7.1 billion in the last 15 years and is projected to reach 11.2 billion by the end of the century. The distribution of humans across the globe has also shifted, with more than 50 percent of the global population now living in urban areas, compared to 29 percent in 1950. Along with these trends, increasing energy demands, expanding industrial activities, and intensification of agricultural activities worldwide have in turn led to changes in emissions that have altered the composition of the atmosphere. These changes have led to major challenges for society, including deleterious impacts on climate, human and ecosystem health. Climate change is one of the greatest environmental challenges facing society today. Air pollution is a major threat to human health, as one out of eight deaths globally is caused by air pollution. And, future food production and global food security are vulnerable to both global change and air pollution. Atmospheric chemistry research is a key part of understanding and responding to these challenges. The Future of Atmospheric Chemistry Research: Remembering Yesterday, Understanding Today, Anticipating Tomorrow summarizes the rationale and need for supporting a comprehensive U.S. research program in atmospheric chemistry; comments on the broad trends in laboratory, field, satellite, and modeling studies of atmospheric chemistry; determines the priority areas of research for advancing the basic science of atmospheric chemistry; and identifies the highest priority needs for improvements in the research infrastructure to address those priority research topics. This report describes the scientific advances over the past decade in six core areas of atmospheric chemistry: emissions, chemical transformation, oxidants, atmospheric dynamics and circulation, aerosol particles and clouds, and biogeochemical cycles and deposition. This material was developed for the NSF's Atmospheric Chemistry Program; however, the findings will be of interest to other agencies and programs that support atmospheric chemistry research.
Keywords: Earth Sciences

Space Studies Board Annual Report 2016 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The original charter of the Space Science Board was established in June 1958, 3 months before the National Aeronautics and Space Administration (NASA) opened its doors. The Space Science Board and its successor, the Space Studies Board (SSB), have provided expert external and independent scientific and programmatic advice to NASA on a continuous basis from NASA's inception until the present. The SSB has also provided such advice to other executive branch agencies, including the National Oceanic and Atmospheric Administration (NOAA), the National Science Foundation (NSF), the U.S. Geological Survey (USGS), the Department of Defense, as well as to Congress. Space Studies Board Annual Report 2016 covers a message from the chair of the SSB, David N. Spergel. This report also explains the origins of the Space Science Board, how the Space Studies Board functions today, the SSB's collaboration with other National Academies of Sciences, Engineering, and Medicine units, assures the quality of the SSB reports, acknowledges the audience and sponsors, and expresses the necessity to enhance the outreach and improve dissemination of SSB reports. This report will be relevant to a full range of government audiences in civilian space research - including NASA, NSF, NOAA, USGS, and the Department of Energy, as well members of the SSB, policy makers, and researchers.
Keywords: Space and Aeronautics

Integrating Social and Behavioral Sciences Within the Weather Enterprise - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Our ability to observe and forecast severe weather events has improved markedly over the past few decades. Forecasts of snow and ice storms, hurricanes and storm surge, extreme heat, and other severe weather events are made with greater accuracy, geographic specificity, and lead time to allow people and communities to take appropriate protective measures. Yet hazardous weather continues to cause loss of life and result in other preventable social costs. There is growing recognition that a host of social and behavioral factors affect how we prepare for, observe, predict, respond to, and are impacted by weather hazards. For example, an individual's response to a severe weather event may depend on their understanding of the forecast, prior experience with severe weather, concerns about their other family members or property, their capacity to take the recommended protective actions, and numerous other factors. Indeed, it is these factors that can determine whether or not a potential hazard becomes an actual disaster. Thus, it is essential to bring to bear expertise in the social and behavioral sciences (SBS)—including disciplines such as anthropology, communication, demography, economics, geography, political science, psychology, and sociology—to understand how people's knowledge, experiences, perceptions, and attitudes shape their responses to weather risks and to understand how human cognitive and social dynamics affect the forecast process itself. Integrating Social and Behavioral Sciences Within the Weather Enterprise explores and provides guidance on the challenges of integrating social and behavioral sciences within the weather enterprise. It assesses current SBS activities, describes the potential value of improved integration of SBS and barriers that impede this integration, develops a research agenda, and identifies infrastructural and institutional arrangements for successfully pursuing SBS-weather research and the transfer of relevant findings to operational settings.
Keywords: Earth Sciences; Behavioral and Social Sciences

Future Water Priorities for the Nation: Directions for the U.S. Geological Survey Water Mission Area - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Solving problems related to use of water resources will be of paramount importance in coming decades as increasing pressure from growing populations, climate change, extreme weather, and aging water-related infrastructure threaten water availability and quality. The Water Mission Area (WMA) of the U.S. Geological Survey (USGS) has a long-established reputation for collecting and delivering high-quality, unbiased scientific information related to the nation's water resources. WMA observations help inform decisions ranging from rapid responses during emergencies such as hurricanes, floods, and forest fires, to the long-term management of water resources. Produced at the request of USGS, this report identifies the nation's highest-priority water science and resources challenges over the next 25 years. Future Water Priorities for the Nation summarizes WMA's current water science and research portfolio, and recommends strategic opportunities for WMA to more effectively address the most pressing challenges.
Keywords: Earth Sciences

A Decision Framework for Managing the Spirit Lake and Toutle River System at Mount St. Helens - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The 1980 eruption of Mount St. Helens in southwest Washington State radically changed the physical and socio-economic landscapes of the region. The eruption destroyed the summit of the volcano, sending large amounts of debris into the North Fork Toutle River, and blocking the sole means of drainage from Spirit Lake 4 miles north of Mount St. Helens. As a result of the blockage, rising lake levels could cause failure of the debris blockage, putting the downstream population of approximately 50,000 at risk of catastrophic flooding and mud flows. Further, continued transport of sediment to the river from volcanic debris deposits surrounding the mountain reduces the flood carrying capacity of downstream river channels and leaves the population vulnerable to chronic flooding. The legacy of the 1980 eruption and the prospect of future volcanic, seismic, and flood events mean that risk management in the Spirit Lake Toutle River system will be challenging for decades to come. This report offers a decision framework to support the long-term management of risks related to the Spirit Lake and Toutle River system in light of the different regional economic, cultural, and social priorities, and the respective roles of federal, tribal, state, and local authorities, as well as other entities and groups in the region. It also considers the history and adequacy of characterization, monitoring, and management associated with the Spirit Lake debris blockage and outflow tunnel, other efforts to control transport of water and sediment from the 1980 and later eruptions, and suggests additional information needed to support implementation of the recommended decision framework.
Keywords: Environment and Environmental Studies; Earth Sciences

Understanding the Long-Term Evolution of the Coupled Natural-Human Coastal System: The Future of the U.S. Gulf Coast - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The U.S. Gulf Coast provides a valuable setting to study deeply connected natural and human interactions and feedbacks that have led to a complex, interconnected coastal system. The physical landscape in the region has changed significantly due to broad-scale, long-term processes such as coastal subsidence and river sediment deposition as well as short-term episodic events such as hurricanes. Modifications from human activities, including building levees and canals and constructing buildings and roads, have left their own imprint on the natural landscape. This coupled natural-human coastal system and the individual aspects within it (physical, ecological, and human) are under increased pressure from accelerating environmental stressors such as sea level rise, intensifying hurricanes, and continued population increase with its accompanying coastal development. Promoting the resilience and maintaining the habitability of the Gulf Coast into the future will need improved understanding of the coupled natural-human coastal system, as well as effective sharing of this understanding in support of decision-making and policies. Understanding the Long-term Evolution of the Coupled Natural-Human Coastal System presents a research agenda meant to enable a better understanding of the multiple and interconnected factors that influence long-term processes along the Gulf Coast. This report identifies scientific and technical gaps in understanding the interactions and feedbacks between human and natural processes, defines essential components of a research and development program in response to the identified gaps, and develops priorities for critical areas of research.
Keywords: Earth Sciences; Environment and Environmental Studies

Soils: The Foundation of Life: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On World Soils Day, December 5, 2016, the U.S. National Committee for Soil Sciences convened a workshop on Soils: The Foundation of Life in Washington, DC. The purpose of the workshop was to increase awareness of the complexity of the roles and great importance of soils to national security, food and nutritional security, water quality and renewability, climate change mitigation and adaptation, human health, biological diversity, and more. This publication highlights the presentations and discussion of the workshop.
Keywords: Policy for Science and Technology

Powering Science: NASA's Large Strategic Science Missions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
NASA's Science Mission Directorate (SMD) currently operates over five dozen missions, with approximately two dozen additional missions in development. These missions span the scientific fields associated with SMD's four divisions—Astrophysics, Earth Science, Heliophysics, and Planetary Sciences. Because a single mission can consist of multiple spacecraft, NASA-SMD is responsible for nearly 100 operational spacecraft. The most high profile of these are the large strategic missions, often referred to as "flagships." Large strategic missions are essential to maintaining the global leadership of the United States in space exploration and in science because only the United States has the budget, technology, and trained personnel in multiple scientific fields to conduct missions that attract a range of international partners. This report examines the role of large, strategic missions within a balanced program across NASA-SMD space and Earth sciences programs. It considers the role and scientific productivity of such missions in advancing science, technology and the long-term health of the field, and provides guidance that NASA can use to help set the priority of larger missions within a properly balanced program containing a range of mission classes.
Keywords: Space and Aeronautics

Antarctic Sea Ice Variability in the Southern Ocean-Climate System: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The sea ice surrounding Antarctica has increased in extent and concentration from the late 1970s, when satellite-based measurements began, until 2015. Although this increasing trend is modest, it is surprising given the overall warming of the global climate and the region. Indeed, climate models, which incorporate our best understanding of the processes affecting the region, generally simulate a decrease in sea ice. Moreover, sea ice in the Arctic has exhibited pronounced declines over the same period, consistent with global climate model simulations. For these reasons, the behavior of Antarctic sea ice has presented a conundrum for global climate change science. The National Academies of Sciences, Engineering, and Medicine held a workshop in January 2016, to bring together scientists with different sets of expertise and perspectives to further explore potential mechanisms driving the evolution of recent Antarctic sea ice variability and to discuss ways to advance understanding of Antarctic sea ice and its relationship to the broader ocean-climate system. This publication summarizes the presentations and discussions from the workshop.
Keywords: Earth Sciences

Frontiers in Soil Science Research: Report of a Workshop - National Research Council (The National Academies Press, 2009)
There has been renewed interest in soil and soil science in recent years as the recognition that biogeochemical processes that occur at the Earth's surface influence global climate change, land degradation and remediation, the fate and transport of nutrients and contaminants, soil and water conservation, soil and water quality, food sufficiency and safety, and many other issues pertinent to the stewardship and conservation of land and water resources. In some areas of the Earth we have approached near irreversible soil conditions that may threaten the existence of future generations. Understanding the long-term implications of decreased soil quality and addressing the aforementioned challenges will require new information based on advances and breakthroughs in soil science research that need to be effectively communicated to stakeholders, policy makers, and the general public. On December 12-14, 2005, the National Academies convened the Frontiers in Soil Science Research Workshop, summarized in this volume, to identify emerging areas for research in soil science by addressing the interaction of soil science subdisciplines, collaborative research with other disciplines, and the use of new technologies in research. The workshop focused around seven key questions addressing research frontiers for the individual soil science disciplines, and also addressing the need for integration across soil science with other disciplines.
Keywords: Earth Sciences

An Astrobiology Strategy for the Search for Life in the Universe - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Astrobiology is the study of the origin, evolution, distribution, and future of life in the universe. It is an inherently interdisciplinary field that encompasses astronomy, biology, geology, heliophysics, and planetary science, including complementary laboratory activities and field studies conducted in a wide range of terrestrial environments. Combining inherent scientific interest and public appeal, the search for life in the solar system and beyond provides a scientific rationale for many current and future activities carried out by the National Aeronautics and Science Administration (NASA) and other national and international agencies and organizations. Requested by NASA, this study offers a science strategy for astrobiology that outlines key scientific questions, identifies the most promising research in the field, and indicates the extent to which the mission priorities in existing decadal surveys address the search for life's origin, evolution, distribution, and future in the universe. This report makes recommendations for advancing the research, obtaining the measurements, and realizing NASA's goal to search for signs of life in the universe.
Keywords: Space and Aeronautics

Recapturing a Future for Space Exploration: Life and Physical Sciences Research for a New Era - National Research Council (The National Academies Press, 2011)
More than four decades have passed since a human first set foot on the Moon. Great strides have been made in our understanding of what is required to support an enduring human presence in space, as evidenced by progressively more advanced orbiting human outposts, culminating in the current International Space Station (ISS). However, of the more than 500 humans who have so far ventured into space, most have gone only as far as near-Earth orbit, and none have traveled beyond the orbit of the Moon. Achieving humans' further progress into the solar system had proved far more difficult than imagined in the heady days of the Apollo missions, but the potential rewards remain substantial. During its more than 50-year history, NASA's success in human space exploration has depended on the agency's ability to effectively address a wide range of biomedical, engineering, physical science, and related obstacles—an achievement made possible by NASA's strong and productive commitments to life and physical sciences research for human space exploration, and by its use of human space exploration infrastructures for scientific discovery. The Committee for the Decadal Survey of Biological and Physical Sciences acknowledges the many achievements of NASA, which are all the more remarkable given budgetary challenges and changing directions within the agency. In the past decade, however, a consequence of those challenges has been a life and physical sciences research program that was dramatically reduced in both scale and scope, with the result that the agency is poorly positioned to take full advantage of the scientific opportunities offered by the now fully equipped and staffed ISS laboratory, or to effectively pursue the scientific research needed to support the development of advanced human exploration capabilities. Although its review has left it deeply concerned about the current state of NASA's life and physical sciences research, the Committee for the Decadal Survey on Biological and Physical Sciences in Space is nevertheless convinced that a focused science and engineering program can achieve successes that will bring the space community, the U.S. public, and policymakers to an understanding that we are ready for the next significant phase of human space exploration. The goal of this report is to lay out steps and develop a forward-looking portfolio of research that will provide the basis for recapturing the excitement and value of human spaceflight—thereby enabling the U.S. space program to deliver on new exploration initiatives that serve the nation, excite the public, and place the United States again at the forefront of space exploration for the global good.
Keywords: Space and Aeronautics

Achieving Science with CubeSats: Thinking Inside the Box - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Space-based observations have transformed our understanding of Earth, its environment, the solar system and the universe at large. During past decades, driven by increasingly advanced science questions, space observatories have become more sophisticated and more complex, with costs often growing to billions of dollars. Although these kinds of ever-more-sophisticated missions will continue into the future, small satellites, ranging in mass between 500 kg to 0.1 kg, are gaining momentum as an additional means to address targeted science questions in a rapid, and possibly more affordable, manner. Within the category of small satellites, CubeSats have emerged as a space-platform defined in terms of (10 cm x 10 cm x 10 cm)- sized cubic units of approximately 1.3 kg each called "U's." Historically, CubeSats were developed as training projects to expose students to the challenges of real-world engineering practices and system design. Yet, their use has rapidly spread within academia, industry, and government agencies both nationally and internationally. In particular, CubeSats have caught the attention of parts of the U.S. space science community, which sees this platform, despite its inherent constraints, as a way to affordably access space and perform unique measurements of scientific value. The first science results from such CubeSats have only recently become available; however, questions remain regarding the scientific potential and technological promise of CubeSats in the future. Achieving Science with CubeSats reviews the current state of the scientific potential and technological promise of CubeSats. This report focuses on the platform's promise to obtain high- priority science data, as defined in recent decadal surveys in astronomy and astrophysics, Earth science and applications from space, planetary science, and solar and space physics (heliophysics); the science priorities identified in the 2014 NASA Science Plan; and the potential for CubeSats to advance biology and microgravity research. It provides a list of sample science goals for CubeSats, many of which address targeted science, often in coordination with other spacecraft, or use "sacrificial," or high-risk, orbits that lead to the demise of the satellite after critical data have been collected. Other goals relate to the use of CubeSats as constellations or swarms deploying tens to hundreds of CubeSats that function as one distributed array of measurements.
Keywords: Space and Aeronautics

Review of the Restructured Research and Analysis Programs of NASA's Planetary Science Division - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The Research and Analysis (R&A) program managed by NASA's Planetary Science Division (PSD), supports a broad range of planetary science activities, including the analysis of data from past and current spacecraft; laboratory research; theoretical, modeling, and computational studies; geological and astrobiological fieldwork in planetary analog environments on Earth; geological mapping of planetary bodies; analysis of data from Earth- and space-based telescopes; and development of flight instruments and technology needed for future planetary science missions. The primary role of the PSD R&A program is to address NASA's strategic objective for planetary science and PSD's science goals. Recently, PSD reorganized the R&A program to provide better alignment with the strategic goals for planetary sciences. The major changes in the R&A program involved consolidating a number of prior program elements, many of which were organized by subdiscipline, into a smaller number of thematic core research program elements. Despite numerous efforts by PSD to communicate the rationale for the reorganization and articulate clearly the new processes, there has been significant resistance from the planetary science community and concerns in some sectors regarding the major realignment of funding priorities. Review of NASA's Planetary Science Division's Restructured Research and Analysis Programs examines the new R&A program and determines if it appropriately aligns with the agency's strategic goals, supports existing flight programs, and enables future missions. This report explores whether any specific research areas or subdisciplinary groups that are critical to NASA's strategic objectives for planetary science and PSD's science goals are not supported appropriately in the current program or have been inadvertently disenfranchised through the reorganization.
Keywords: Space and Aeronautics

Space Studies Board Annual Report 2017 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The original charter of the Space Science Board was established in June 1958, three months before the National Aeronautics and Space Administration (NASA) opened its doors. The Space Science Board and its successor, the Space Studies Board (SSB), have provided expert external and independent scientific and programmatic advice to NASA on a continuous basis from NASA's inception until the present. The SSB has also provided such advice to other executive branch agencies, including the National Oceanic and Atmospheric Administration (NOAA), the National Science Foundation (NSF), the U.S. Geological Survey (USGS), the Department of Defense, as well as to Congress. Space Studies Board Annual Report 2017 covers a message from the chair of the SSB, David N. Spergel. This report also explains the origins of the Space Science Board, how the Space Studies Board functions today, the SSB's collaboration with other National Academies of Sciences, Engineering, and Medicine units, assures the quality of the SSB reports, acknowledges the audience and sponsors, and expresses the necessity to enhance the outreach and improve dissemination of SSB reports. This report will be relevant to a full range of government audiences in civilian space research - including NASA, NSF, NOAA, USGS, and the Department of Energy, as well members of the SSB, policy makers, and researchers.
Keywords: Space and Aeronautics

Thriving on Our Changing Planet: A Decadal Strategy for Earth Observation from Space - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
We live on a dynamic Earth shaped by both natural processes and the impacts of humans on their environment. It is in our collective interest to observe and understand our planet, and to predict future behavior to the extent possible, in order to effectively manage resources, successfully respond to threats from natural and human-induced environmental change, and capitalize on the opportunities – social, economic, security, and more – that such knowledge can bring. By continuously monitoring and exploring Earth, developing a deep understanding of its evolving behavior, and characterizing the processes that shape and reshape the environment in which we live, we not only advance knowledge and basic discovery about our planet, but we further develop the foundation upon which benefits to society are built. Thriving on Our Changing Planet presents prioritized science, applications, and observations, along with related strategic and programmatic guidance, to support the U.S. civil space Earth observation program over the coming decade.
Keywords: Space and Aeronautics

Environmental Engineering for the 21st Century: Addressing Grand Challenges - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Environmental engineers support the well-being of people and the planet in areas where the two intersect. Over the decades the field has improved countless lives through innovative systems for delivering water, treating waste, and preventing and remediating pollution in air, water, and soil. These achievements are a testament to the multidisciplinary, pragmatic, systems-oriented approach that characterizes environmental engineering. Environmental Engineering for the 21st Century: Addressing Grand Challenges outlines the crucial role for environmental engineers in this period of dramatic growth and change. The report identifies five pressing challenges of the 21st century that environmental engineers are uniquely poised to help advance: sustainably supply food, water, and energy; curb climate change and adapt to its impacts; design a future without pollution and waste; create efficient, healthy, resilient cities; and foster informed decisions and actions.
Keywords: Engineering and Technology; Earth Sciences